THE ROLE OF HUMAN RESOURCE MANAGEMENT IN INCREASING PRODUCTIVITY - Eloh Bahiroh; Sri Ndaru Arthawati; Fatika Andaristi; Najla Indira Faradiva; Andi (Adisam Publisher, 2024)
Human Resource Management (HRM) has a significant impact on improving employee productivity through various strategic practices. Careful recruitment processes ensure that hired employees have the skills and capabilities to fit the company culture, thereby reducing turnover and increasing efficiency. Ongoing training and effective performance appraisals help workers develop competencies and stay motivated to achieve their targets. In addition, a positive company culture and effective communication play an important role in creating a supportive work environment, which in turn encourages collaboration and innovation. Supporting work-life balance and implementing HR management technologies, such as human resource management systems (HRMS) and e-education platforms, also improve worker satisfaction and retention, while enabling higher operational efficiency. With an integrated approach that combines recruitment practices, training, corporate culture, and technology, HR management can create a productive work environment that supports superior performance and business sustainability.